PERAN PENJUALAN DALAM PERUSAHAAN - Arief, Muhammad (Lembaga Penerbitan Unversitas Esa Unggul, 2017)
Company products are generally not original products, but follow a kind that has been widely on the market. Consumers do not know many of the benefits of the company, but generally follow the appropriate products according to him. The company's sales management with its program works hard to achieve the company's marketing goals so that potential customers can be touched & moved to buy the company's service products. The seller will pursue the number of sales figures in the target market as much as possible as a means of achieving marketing objectives. Sales policies in running its activities do not act alone, but play an important role in the company's marketing program. Sales play an important role when creating business plans, personal sales policies, distribution policies, relational marketing practices & customer relationship management. Sales is a series of processes that continue the company's marketing process.Â Keywords: sales, sales & distribution, sales & marketing.